Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the inequality [tex]\(6h - 5(h - 1) \leq 7h - 11\)[/tex], we will follow several algebraic steps. Here is the detailed, step-by-step solution:
1. Distribute the [tex]\(-5\)[/tex] within the parentheses on the left-hand side:
[tex]\[ 6h - 5(h - 1) \leq 7h - 11 \][/tex]
[tex]\[ 6h - 5h + 5 \leq 7h - 11 \][/tex]
2. Combine like terms on the left-hand side:
[tex]\[ (6h - 5h) + 5 \leq 7h - 11 \][/tex]
[tex]\[ h + 5 \leq 7h - 11 \][/tex]
3. Move the variable terms involving [tex]\(h\)[/tex] to one side and constants to the other side by subtracting [tex]\(7h\)[/tex] from both sides:
[tex]\[ h + 5 - 7h \leq -11 \][/tex]
[tex]\[ -6h + 5 \leq -11 \][/tex]
4. Isolate the variable term by subtracting [tex]\(5\)[/tex] from both sides:
[tex]\[ -6h + 5 - 5 \leq -11 - 5 \][/tex]
[tex]\[ -6h \leq -16 \][/tex]
5. Divide both sides of the inequality by [tex]\(-6\)[/tex] and remember to reverse the inequality sign (since dividing by a negative number reverses the inequality sign):
[tex]\[ h \geq \frac{-16}{-6} \][/tex]
[tex]\[ h \geq \frac{16}{6} \][/tex]
6. Simplify the fraction:
[tex]\[ h \geq \frac{16}{6} = \frac{8}{3} \][/tex]
The solution to the inequality [tex]\(6h - 5(h - 1) \leq 7h - 11\)[/tex] is [tex]\(h \geq \frac{8}{3}\)[/tex].
In interval notation, this solution is written as:
[tex]\[ \left[\frac{8}{3}, \infty\right) \][/tex]
Thus, the answer:
- The solution in terms of [tex]\(h\)[/tex]: [tex]\(h \geq \frac{8}{3}\)[/tex]
- The solution in interval notation: [tex]\(\left[\frac{8}{3}, \infty\right)\)[/tex]
1. Distribute the [tex]\(-5\)[/tex] within the parentheses on the left-hand side:
[tex]\[ 6h - 5(h - 1) \leq 7h - 11 \][/tex]
[tex]\[ 6h - 5h + 5 \leq 7h - 11 \][/tex]
2. Combine like terms on the left-hand side:
[tex]\[ (6h - 5h) + 5 \leq 7h - 11 \][/tex]
[tex]\[ h + 5 \leq 7h - 11 \][/tex]
3. Move the variable terms involving [tex]\(h\)[/tex] to one side and constants to the other side by subtracting [tex]\(7h\)[/tex] from both sides:
[tex]\[ h + 5 - 7h \leq -11 \][/tex]
[tex]\[ -6h + 5 \leq -11 \][/tex]
4. Isolate the variable term by subtracting [tex]\(5\)[/tex] from both sides:
[tex]\[ -6h + 5 - 5 \leq -11 - 5 \][/tex]
[tex]\[ -6h \leq -16 \][/tex]
5. Divide both sides of the inequality by [tex]\(-6\)[/tex] and remember to reverse the inequality sign (since dividing by a negative number reverses the inequality sign):
[tex]\[ h \geq \frac{-16}{-6} \][/tex]
[tex]\[ h \geq \frac{16}{6} \][/tex]
6. Simplify the fraction:
[tex]\[ h \geq \frac{16}{6} = \frac{8}{3} \][/tex]
The solution to the inequality [tex]\(6h - 5(h - 1) \leq 7h - 11\)[/tex] is [tex]\(h \geq \frac{8}{3}\)[/tex].
In interval notation, this solution is written as:
[tex]\[ \left[\frac{8}{3}, \infty\right) \][/tex]
Thus, the answer:
- The solution in terms of [tex]\(h\)[/tex]: [tex]\(h \geq \frac{8}{3}\)[/tex]
- The solution in interval notation: [tex]\(\left[\frac{8}{3}, \infty\right)\)[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.